Advancing Quality and Safety Culture in Healthcare: Insights From the Evaluation of an Improvement Science Program for Nurses and Midwives. - Archer, Yasmine; Chasle, Briony; Macpherson, Amanda; Wilson, Val (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2025)
Aims: This paper presents the outcomes and insights gained from the implementation of an Improvement Science program tailored for nursing and midwifery staff within a large local health district in New South Wales. The programme aimed to enhance frontline clinicians' confidence and capability in quality improvement, ultimately improving patient outcomes and safety culture. Design: Through an explanatory sequential mixed‐methods evaluation study, we assessed the programme's effectiveness in building capacity, sustaining practice changes and fostering a culture of continuous improvement. Methods: Quantitative data were collected through pre‐post knowledge surveys, post workshop feedback and programme participation rates. Qualitative data were then collected via nine interviews with programme participants. Simple descriptive statistical analysis for quantitative data and a thematic analysis of qualitative data was undertaken. Data were then integrated from these multiple sources to gain a deeper understanding of the outcomes of the Improvement Science Program. Results: Key findings indicate that coaching and mentoring support significantly contributed to project completion and sustained practice changes. Structured coaching sessions, collaborative team meetings, and executive sponsorship were vital components that facilitated successful outcomes. Notably, effective leadership, often demonstrated by Clinical Nurse Educators and Consultants, played a crucial role in fostering staff collaboration and participation. Insights from qualitative interviews highlight the transformative impact of the programme on participants' skills, confidence and practice. Conclusion: The paper concludes with recommendations for future Improvement Science programs, emphasising the importance of structured coaching, accountability mechanisms, and the identification and support of future coaches. Overall, this study underscores the value of ongoing training initiatives in promoting a culture of safety, quality improvement and enhanced patient outcomes in healthcare settings. Patient or Public Contribution: This study had no patient or public contribution. Reporting Method: Adherence to Standards for Reporting Qualitative Research (SRQR) EQUATOR guidelines (see Supplementary file).